2020
DOI: 10.3174/ajnr.a6719
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution and Role of M1 and M2 Macrophages in Aneurysm Healing after Platinum Coil Embolization

Abstract: BACKGROUND AND PURPOSE: Impairment of macrophage polarization from a proinflammatory macrophage type 1 (M1) population to an anti-inflammatory macrophage type 2 (M2) population is a hallmark of poor wound healing. In this study, we aimed to evaluate the distribution of M1 and M2 macrophages and to analyze their association with healing in aneurysms embolized by endovascular coiling. MATERIALS AND METHODS: Elastase-induced aneurysms were created in female rabbits and subsequently embolized with platinum coils. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The porous structure is hypothesized to serve as a scaffold that promotes stable clot formation and provides support for the remodeling of this clot to a connective tissue matrix. There is a growing body of evidence that biomaterials and variations of their structure and chemical properties may influence the phenotype of macrophages responding to the implant 15–21 . Increased surface roughness and increased interconnected porosity are both documented drivers of M2‐like activation, and a pro‐regenerative macrophage phenotype 30,31 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The porous structure is hypothesized to serve as a scaffold that promotes stable clot formation and provides support for the remodeling of this clot to a connective tissue matrix. There is a growing body of evidence that biomaterials and variations of their structure and chemical properties may influence the phenotype of macrophages responding to the implant 15–21 . Increased surface roughness and increased interconnected porosity are both documented drivers of M2‐like activation, and a pro‐regenerative macrophage phenotype 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence that biomaterials and variations of their structure and chemical properties may influence the phenotype of macrophages responding to the implant. [15][16][17][18][19][20][21] Increased surface roughness and increased interconnected porosity are both documented drivers of M2-like activation, and a pro-regenerative macrophage phenotype. 30,31 Some studies have suggested that the macrophage phenotypes present in the foreign body response may determine the outcome of the implant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Macrophages are key players in the wound healing response following embolization of aneurysms. 24 Macrophages exist in a continuum of activation states, flanked on either end by pro-inflammatory (M1-like) and prohealing (M2-like) activation. Macrophages also secrete a variety of soluble cues to coordinate the wound healing response in other cell types, especially fibroblasts.…”
Section: Introductionmentioning
confidence: 99%